PENGARUH STRUKTUR MODAL DALAM MEMEDIASI HUBUNGAN ANTARA DIVERSFIKASI TERHADAP KINERJA KEUANGAN PERUSAHAAN - Agustian, Aditya Nur; Ramadhan, Fakhrizal; Aulia, Hanifa; Sulistyorini, Dyah Ayu; Pratiwi, Monica Weni (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2023)
The purpose of this study was to examine the direct effect of diversification and capital structure variables on financial performance, as well as the indirect effect of capital structure on company financial performance. The population of this research is the automotive and component companies listed on the Indonesia Stock Exchange in the 2015-2019 period amounting to 65. The sampling technique used is the purposive sampling method. The data analysis method used was path analysis and Sobel test using SPSS software. The results show that diversification does not affect the capital structure, diversification and capital structure affect the company's financial performance, and capital structure does not mediate the relationship between diversification and the company's financial performance. The limitation in this study is that it only uses one type of measurement of the company's financial performance. The results of this study are expected to contribute to the field of financial accounting.Keywords: Capital Structure, Diversification, Financial Performance